Nanosilver induces a non-culturable but metabolically active state in Pseudomonas aeruginosa - Königs, Alexa M.; Flemming, Hans-Curt; Wingender, Jost (Frontiers in Microbiology, 2015)
The antimicrobial properties of silver nanoparticles (AgNPs) have raised expectations for the protection of medical devices and consumer products against biofilms. The effect of silver on bacteria is commonly determined by culture-dependent methods. It is as yet unknown if silver-exposed bacteria can enter a metabolically active but nonculturable state. In this study, the efficacy of chemically synthesized AgNPs and silver as silver nitrate (AgNO3) against planktonic cells and biofilms of the facultative pathogen Pseudomonas aeruginosa was investigated in microtiter plate assays, using cultural as well as culture-independent methods. In liquid medium, AgNPs and AgNO3 inhibited both planktonic growth and biofilm formation. The efficacy of AgNPs and AgNO3 against established, 24 h-old biofilms and planktonic stationary-phase cells was compared by exposure to silver in deionized water. Loss of culturability of planktonic cells was always higher than that of the attached biofilms. However, resuspended biofilm cells became more susceptible to AgNPs and AgNO3 than attached biofilms. Thus, the physical state of bacteria within biofilms rendered them more tolerant to silver compared with the planktonic state. Silver-exposed cells that had become unculturable still displayed signs of viability: they contained ribosomal RNA, determined by fluorescent in situ hybridization, as an indicator for potential protein synthesis, maintained their membrane integrity as monitored by differential live/dead staining, and displayed significant levels of adenosine triphosphate. It was concluded that AgNPs and AgNO3 in concentrations at which culturability was inhibited, both planktonic and biofilm cells of P. aeruginosa were still intact and metabolically active, reminiscent of the viable but nonculturable state known to be induced in pathogenic bacteria in response to stress conditions. This observation is important for a realistic assessment of the antimicrobial properties of AgNPs.